DESKRIPSI UJI BERKALA KENDARAAN BERMOTOR MOBIL BUS ANTAR KOTA, DAMPAK EKONOMI DAN POTENSI KECELAKAAN LALU LINTAS DALAM DIMENSI PELAKU USAHA OTOBUS (STUDI KASUS TRAYEK IRISAN SOLO – SEMARANG) - Kawangmani, Mikha Ekapaksi Putra; Pratama, Yogi Pasca; Samudro, Bhimo Rizky (EP FEB UNS, 2017)
The background of this study is society needs in modern age which needs of transportation to support their activity. Transportation in Indonesia, especially mass transport that exist today seen not good. Government as supervision holder in public policy be charged to give clear regulation, implement and improvement services of mass transportation which is integrated and become positive impact.Operational pattern of transport venture that their business be regulated by government through law expected capable to implement that in the field. However, in fact, many transport venture that doing principle of effective and efficient with ignore a standard which be appointed by the government through ministry of transportation. Route Solo – Semarang with variety of activity inside it, for many sector as tourism, farming, industry and creative economy need mass transportation. This study uses methodology of qualitative research with phenomenology perspective in field about public policy in transportation sector. That public policy refer to policy about implement of technical standardization for vehicle and periodic test for intercity bus for incision route Solo – Semarang. Periodic test for vehicle policy to transport venture intend to find out implementation of periodic test for vehicle, to transport venture in incision route Solo-Semarang, along economy impact to people and to transport venture.Government Policy of Periodic Vehicle Rule has been make negatif effect for public transportation if it can’t be allowed. Keywords: Superbus Venture, Public Economy, Society as Consumer